Shipboard ADCP current measurements (75 kHz) during RV METEOR cruise M187 - Cardoso, Cláudio; Kopte, Robert; Browning, Thomas J; Dengler, Marcus (PANGAEA, 2023)
Current velocities of the upper water column along the cruise track of R/V Meteor III cruise MET187 were collected by a vessel-mounted 75 kHz RDI Workhorse Long Ranger ADCP. The ADCP transducer was located at 5.0 m below the water line. The instrument was operated in broadband mode (WM1) with two different configurations: (1 - corresponding to met_187_vmadcp_75khz_01.nc) bin size: 5.0 m, blanking distance: 2.0 m, number of bins: 128, vertical range: 12.0 m - 647.0 m; (2 - corresponding to met_187_vmadcp_75khz_0[2,3].nc) bin size: 8.0 m, blanking distance: 4.0 m, number of bins: 100, vertical range: 17.0 - 809.0 m. Heading, pitch and roll data from the ship's motion reference unit and the navigation data from the Global Positioning systems were used by the data acquisition software VmDAS internally to convert ADCP velocities into earth coordinates. Single-ping data / ping ensembles were screened for bottom signals and, where appropriate, a bottom mask was manually processed. The ship's velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship's heading data. Further errors stem from a misalignment of the transducer with the ship's centerline. For technical reasons, the transducer was lifted from the moonpool on February 18th, 2023. Therefore, two separate calibrations were carried out: Data post-processing included water track calibration of the misalignment angle and scale factor of the Ocean Surveyor signal. For technical reasons, the transducer was lifted from the moonpool on February 18th, 2023. Therefore, two separate calibrations were carried out: prior February 18th, 2023 (corresponding to met_187_vmadcp_75khz_0[1,2].nc): misalignment angle of -41.8717° +/- 0.4333° (0.5755°), scale factor of 1.0001 +/- 0.0064 (0.0079); after February 18th, 2023 (corresponding to met_187_vmadcp_75khz_03.nc): misalignment angle of -41.8071° +/- 0.5600°, scale factor of 0.9971 +/- 0.0074. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on following threshold criteria: abs(UC) or abs(VC) > 1.5 m/s, rms(UC_z) or rms(VC_z) > 0.3.